Kualitas Lingkungan dan Personal Hygiene Terhadap Kejadian Scabies pada Warga Binaan Lapas Rantauprapat - Safrina Ramadhani; Rupina K Situmorang; Rosdiana Rosdiana (LPPM STIKES Siti Hajar dan Insight Power, 2022)
Prison, or more commonly known as prison, is always synonymous with a crowded room, not so well maintained and lacking ventilation, so it is very likely that various diseases will arise. Data from the data from the Class IIA Rantauprapat Prison in Labuhan Batu Regency in 2019 were inhabited by 1,532 people and there were 36 cases of scabies. The purpose of this study was to determine the relationship between the physical quality of the environment and personal hygiene on the incidence of scabies among assisted residents in Class IIA Rantauprapat Prison in 2020.The research design used was an analytic study with a cross sectional approach. The study population was all male assisted residents in the Class IIA Rantauprapat Prison, Labuhan Batu Regency in 2020, as many as 1,018 people. Sampling using a purposive sampling system 91 people. Data analysis used univariate and bivariate analysis.The results of the study with bivariate analysis showed that the p value of each variable, namely the occupancy density variable was 0.008, the humidity was 0.018, the temperature was 0.008, the ventilation was 0.019 and personal hygiene was 0.000.The conclusion of this study is that there is a relationship between occupancy density, humidity, temperature, ventilation and personal hygiene with the incidence of scabies in Class IIA Rantauprapat Prison in 2020. It is recommended that Class IIA Rantauprapat Prison improve counseling from health workers and provide treatment for assisted residents in Class Prisons. IIA Rantauprapat who suffered from scabies completely so that it did not spread to other inmates.Keywords: Physical Environment, Personal Hygiene, Scabies, Prison, Rantauprapat